Poles of Painlevé IV Rationals and their Distribution - Masoero, D.; Roffelsen, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We study the distribution of singularities (poles and zeros) of rational solutions of the Painlevé IV equation by means of the isomonodromic deformation method. Singularities are expressed in terms of the roots of generalised Hermite Hm,n and generalised Okamoto Qm,n polynomials. We show that roots of generalised Hermite and Okamoto polynomials are described by an inverse monodromy problem for an anharmonic oscillator of degree two. As a consequence, they turn out to be classified by the monodromy representation of a class of meromorphic functions with a finite number of singularities introduced by Nevanlinna. We compute the asymptotic distribution of roots of the generalized Hermite polynomials in the asymptotic regime when m is large and n fixed.